Comparative analysis of IscM and IscQu in feline oral squamous cell carcinoma treatment: cytotoxic and apoptotic insights - Cakiroglu, Huseyin; Deveci Ozkan, Asuman; Erman, Gulay; Bozkurt, Mehmet Fatih; Yanar, Sevinc; Kale Bakir, Elif; Yuzugullu Karakus, Yonca (Frontiers in Veterinary Science, 2025)
BackroundFeline oral squamous cell carcinoma (FOSCC) is the most common malignant oral tumor in cats, characterized by invasive and aggressive behavior regardless of its location. Conventional treatments, including surgery, radiation therapy, and chemotherapy, often yield unsatisfactory outcomes, with tumor progression and tissue destruction frequently leading to euthanasia. In anthroposophical medicine, extracts of Viscum album have been developed as complementary cancer treatments, with Iscador, the oldest and most widely used oncological drug, showing promising anticancer potential. This study investigated, for the first time, the cytotoxic and apoptotic effects of IscM and IscQu, two Viscum album extracts, on FOSCC cells.MethodsUsing primary cultures of three FOSCC cell lines, cell viability assays were performed to assess cytotoxicity, and the effects on apoptotic cell death, cell cycle arrest, and cellular and nuclear morphology were evaluated. Additionally, mRNA expression levels of Cyclin D, Cdk4, Bcl-2, Bax, and p53 were analyzed.ResultsThe results revealed that both IscM and IscQu induced apoptotic cell death and promoted cell cycle arrest in all three FOSCC cell lines tested. IscQu exhibited relatively stronger pro-apoptotic effects compared to IscM, although no significant differences were observed among the cell lines.ConclusionThese findings suggest that Viscum album extracts, particularly IscQu, may exert anti-tumor effects on feline oral squamous cell carcinoma cells in vitro.